2020
DOI: 10.3389/fimmu.2020.02158
|View full text |Cite
|
Sign up to set email alerts
|

BTK Inhibition Impairs the Innate Response Against Fungal Infection in Patients With Chronic Lymphocytic Leukemia

Abstract: Infections represent a cause of morbidity and mortality in patients affected by chronic lymphocytic leukemia (CLL). Introduction of new drugs in CLL clinical practice has showed impressive efficacy, in particular those targeting BTK. Among the consistent clinical data, an increasing number of reports describing the occurrence of unexpected opportunistic fungal infections has been reported during treatment with ibrutinib in the first 6 months of treatment. The reason underlying manifestations of invasive fungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…A TLR9-dependent endosomally driven pathway was implicated to increase the susceptibility of patients on ibrutinib to IFI ( Bercusson et al, 2018 ). A recent report ( Fiorcari et al, 2020 ), shows that ibrutinib- or acalabrutinib-mediated BTK inhibition negatively affects CLL-associated macrophages during A. fumigatus infection. It was also reported that ibrutinib and acalabrutinib impaired M1 polarization in macrophages, a phenotype associated with an efficient anti−microbial immune response ( Colado et al, 2020 ).…”
Section: Mechanisms Underlying Increased Incidence Of Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A TLR9-dependent endosomally driven pathway was implicated to increase the susceptibility of patients on ibrutinib to IFI ( Bercusson et al, 2018 ). A recent report ( Fiorcari et al, 2020 ), shows that ibrutinib- or acalabrutinib-mediated BTK inhibition negatively affects CLL-associated macrophages during A. fumigatus infection. It was also reported that ibrutinib and acalabrutinib impaired M1 polarization in macrophages, a phenotype associated with an efficient anti−microbial immune response ( Colado et al, 2020 ).…”
Section: Mechanisms Underlying Increased Incidence Of Infectionsmentioning
confidence: 99%
“…Off-BTK effects in B- or non-B-cells have a therapeutic potential and they may also account for the observed AEs, since those cannot be explained by BTK inhibition alone. As will be discussed in greater detail below, binding to BTK in B-cell malignancies has a treatment effect, while inhibition of this kinase by BTKi in macrophages or neutrophils was suggested to impair the anti-fungal response ( Fiorcari et al, 2020 ). However, it should be pointed out that in X-linked agammaglobulinemia, defined by non-functional BTK, a similar overt propensity for invasive fungal infections is not seen, nor are there increased bleedings, skin manifestations, diarrhoeas or cardiovascular disease ( Smith and Berglöf, 1993 ; Ochs and Smith, 1996 ).…”
Section: Brief Introductory Overview To Adverse Effectsmentioning
confidence: 99%
“…Recently, invasive fungal infections have been reported among patients receiving treatment with ibrutinib. In this scenario, ibrutinib is able to affect the ability of NLC to counteract Aspergillus fumigatus conidia germination due to reduced phagocytosis and the impairment of a productive inflammatory response with a decreased level of IL-1β and TNF-α [ 81 , 82 ].…”
Section: Introductionmentioning
confidence: 99%
“…While BTK inhibition may supress the excessive in ammation caused by the innate immune response against SARS-CoV-2, it may also increase the risk for secondary infections. Fungal and other opportunistic infections such as pneumonia have been observed in CLL and other patients on ibrutinib [23,[50][51][52]. However concomitant use of CD20-depleting agents may confound such a risk since CD20-depleting agents are also associated with an increased risk of pneumonia [53].…”
Section: Discussionmentioning
confidence: 99%